2019
DOI: 10.2478/jwld-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

Role of drainage layer on green roofs in limiting the runoff of rainwater from urbanized areas

Abstract: Green roofs play a significant role in sustainable drainage systems. They form absorbent surfaces for rainwater, which they retain with the aid of profile and plants. Such roofs therefore take an active part in improving the climatic conditions of a city and, more broadly, the water balance of urbanized areas. One of the factors influencing the hydrological efficiency of green roofs is the drainage layer. In the article, column studies were carried out under field conditions involving the comparison of the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, however, they reported not statistically significant correlation between ADWP and retention, but their research was conducted in natural conditions and they have taken into account all precipitations having diversified depths and intensities [40]. In another publication Baryla [41] found that the volume of precipitation, the initial moisture substrate, and ADWP have a significant effect on green roof retention. But she reported the higher correlation of retention with moisture content than with the ADWP.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, however, they reported not statistically significant correlation between ADWP and retention, but their research was conducted in natural conditions and they have taken into account all precipitations having diversified depths and intensities [40]. In another publication Baryla [41] found that the volume of precipitation, the initial moisture substrate, and ADWP have a significant effect on green roof retention. But she reported the higher correlation of retention with moisture content than with the ADWP.…”
Section: Resultsmentioning
confidence: 97%
“…Baryla [49] monitored six test stands for column studies to compare the retention capacity of two different types of green roof drainage layer: Leca® and quartzite grit. Each type has 10 cm and 5cm drainage layer columns.…”
Section: Substrate Layermentioning
confidence: 99%
“…A properly constructed GR system serves two primary functions related to stormwater management; a GR can reduce the amount of stormwater runoff through its water retention capacity, as well as delay the peak flow of runoff, alleviating the pressures on stormwater infrastructures. These characteristics and effects of GR substrate layers and drainage materials have been extensively studied [2,3].…”
Section: Introductionmentioning
confidence: 99%